Characteristic and sources of atmospheric ozone in Xi'an. Issue 9 (November 2019) - Liu, Song; Cheng, Yan; Yan, Lu; Yu, Chuck Wah
The atmospheric ozone (O3 ) is a serious pollution particularly in summer that causes serious respiratory health effect on residents and economic impact on sustainable development of Xi'an. The purpose of this project is to provide monitored data to determine the extent of O3 pollution in Xi'an and contributions of local and regional sources; which is different to other cities in China. Continuous monitoring of near-surface concentrations of ozone in ambient environment was conducted from March 2016 to June 2017 using UV photometric O3 analysers. The annual average O3 concentration was 37.2 μg·m −3 (1.0–120.3 μg·m −3 ). Higher average O3 concentrations were recorded in summer (59.2 μg·m −3 ) and spring (54.1 μg·m −3 ) than in autumn (30.7 μg·m −3 ) and winter (19.1 μg·m −3 ). The 1 h average O3 concentration during seven-months monitoring, mainly during May (38 h) and June (31 h) surpassed the National Ambient Air Quality Standard of 160 μg·m −3 (GB 3095–2012). The regional pollution is important during daytime (peaked at 16:00) and was 18% higher than at night. The O3 /NO x ratios ranged from 0 to 6.3, and 99.99% were <5. Results show the significant impact of regional sources of O3, which were mainly due to biogenic volatile organic compounds emitted from forests in surrounding mountains. Meteorological factors, e.g. solar irradiance, humidity, temperature and atmospheric pressure also have important effects on ambient O3 concentrations.